Survivors : CAMBODIAN REFUGEES IN THE UNITED STATES - Chan, Sucheng (Book collections on Project MUSE., 2004)
"In this clear, comprehensive, and unflinching study, Sucheng Chan invites us to follow the saga of Cambodian refugees striving to distance themselves from a series of cataclysmic events in their homeland. Survivors tracks not only the Cambodians' fight for their lives but also their battle for self-definition in new American surroundings. Unparalleled in scope, Survivors begins with the Cambodians' experiences under the brutal Khmer Rouge regime, following them through escape to refugee camps in Thailand and finally to the United States, where they try to build new lives in the wake of massive trauma. Their struggle becomes primarily economic as they continue to negotiate new cultures and deal with rapidly changing gender and intergenerational relations within their own families. Poverty, crime, and racial discrimination all leave impact on their experiences in America, and each is examined in depth. Although written as a history, this is a thoroughly multidisciplinary study, and Chan makes use of research from anthropology, sociology, psychology, medicine, social work, linguistics and education. She also captures the perspective of individual Cambodians. Drawing on interviews with more than fifty community leaders, a hundred government officials, and staff members in volunteer agencies, Survivors synthesizes the literature on Cambodian refugees, many of whom come from varying socioeconomic backgrounds. A major scholarly achievement, Survivors is unique in the Asian American canon for its memorable presentation of cutting-edge research and its interpretation of both sides of the immigration process."